CARDIOPULMONARY EXCERSISE TESTING IN RISK STRATIFICATION IN PATIENTS WITH PULMONARY ARTERIAL HYPERTENSION AND CHRONIC THROMBOEMBOLIC PULMONARY HYPERTENSION - I. N. Taran; Z. S. Valieva; T. V. Martynyuk; I. Ye. Chazova (Евразийский Кардиологический Журнал, 2017)
In recent years the information about relevance of cardiopulmonary exercise testing (CPET) in complex assessment of pulmonary arterial hypertension (PAH) patients and chronic thromboembolic pulmonary hypertension (CTEPH) patients have been accumulating. Parameters of CPET, such as peak oxygen consumption (Vo2 peak) and ventilation equivalents (VE/Vco2) are very important in risk stratification in patients with PAH, also as distance in 6-minute walking test, the echocardiography and right heart catheterization results, N-terminal prohormone of natriuretic peptide according to the European Society of Cardiology and European Respiratory Society guidelines on diagnosis and treatment of pulmonary hypertension. However, there are no parameters, which can be used in clinical practice to reflect the risk of mortality during 1 year in patients with CTEPH. The aim of our study was to assess the role of CPET in risk stratification, achieving therapy goals and making decision about therapy escalation in patients with PAH and CTEPH. Results of our pilot study demonstrated, that CPET parameters are the reliable markers to reflect the PAH and CTEPH progression. The CPET is necessary for pathogenic therapy efficacy assessment and for making decision of therapy escalation in patients with PAH, also as in CTEPH patients. The critical role of CPET in risk stratification in PAH and CTEPH patients should be emphasized.